Penerapan Model PjBL untuk Meningkatkan Hasil Belajar P5 dengan Media Papan Pintar Kelas II SD - Kurniayu Maduratih; Afakhrul Masub Bakhtiar (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Elementary school students generally have the characteristics of being happy to play, happy to move, happy to work in groups and happy to demonstrate things directly. Therefore, educational practices must undergo a transformation to be more student-centered and encourage active student participation through the use of learning models or media that are appropriate and suitable for elementary school students. This media was created taking into account second grade elementary school students. To help students better understand the meaning of each Pancasila principle, researchers developed the Pancasila Smart Board Media as a teaching aid. By using the Pancasila smart board media. The aim of this research is to improve the learning outcomes of Pancasila education for class II students at UPT SDN 12 Gresik with a total of 25 students. This research uses classroom action research methods through observation, tests and field notes. Each cycle consists of Planning, Action, Observation and Reflection. To analyze test results regarding student learning outcomes, researchers added up the scores for each component according to traditional evaluations regarding the percentage of learning completion. There was an increase in student learning outcomes, namely, in the pre-cycle the percentage was still 40%, and in the first cycle it rose to 72% and in the second cycle it became very good with a percentage of 100%. After three cycles, finally the learning outcomes assessment reached 100% in cycle II, which shows success. Class II students at UPT SDN 12 Gresik can use the Pancasila smart board media to improve their learning outcomes.